MEMPROGRAMKAN AKSES PEMBIAYAAN SYARIAH BAGI USAHA MIKRO KECIL DAN MENENGAH DI DESA CIBITUNG WETAN, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Ria Kusumaningrum; Ratu Dinny; Muhammad Ryandika Zulkarnaen (SAHID DEVELOPMENT JOURNAL, 2023)
The traditional manufacture of palm sugar in Cibitung Wetan Village, Pamijahan District, Bogor Regency, is carried out by many Micro, Small and Medium Enterprises or MSMEs by making it from palm sap which comes from the male flower bunches of palm palm trees or sugar palms which are left to let the juices out of palm trees, such as coconut, and palm trees. In making sugar, MSMEs finance independently. The government has not been involved much in capitalizing MSMEs. MSMEs hope for investment from other parties. Palm sugar production requires capital. Therefore, cooperation between MSMEs is needed so that they can compete with other vegetable material processing businesses. In such cases, sharia financing can enter the palm sugar manufacturing business.